2019
DOI: 10.1111/jsap.12978
|View full text |Cite
|
Sign up to set email alerts
|

Development of a perceived exertion scale for dogs using selected physiologic parameters

Abstract: Objective To develop a perceived exertion scale for dogs exercising on a treadmill and to assess intra‐ and inter‐observer variability. Materials and Methods Fifteen healthy client‐owned dogs participated in paired exercise trials. Measurements of lactate, glucose, heart rate, temperature, respiratory rate and regional tissue oximetry were obtained before, during and after exercise. Perceived exertion scale scores were recorded during exercise and using video recordings to evaluate inter‐observer variability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…e reasons why there is no association between the speed of activity and HR are not clear, but the lower and narrow range of exercise intensity may be involved. e treadmill speed in our protocols 1 to 6 was set at 4.8-6.4 km/ h, which is similar to that of the study by Swanson et al [38]. In this study, they demonstrated that the dogs were easily distracted at a lower treadmill speed, and the HR at a lower range of speed could hardly reflect exercise intensity [38].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…e reasons why there is no association between the speed of activity and HR are not clear, but the lower and narrow range of exercise intensity may be involved. e treadmill speed in our protocols 1 to 6 was set at 4.8-6.4 km/ h, which is similar to that of the study by Swanson et al [38]. In this study, they demonstrated that the dogs were easily distracted at a lower treadmill speed, and the HR at a lower range of speed could hardly reflect exercise intensity [38].…”
Section: Discussionsupporting
confidence: 66%
“…e treadmill speed in our protocols 1 to 6 was set at 4.8-6.4 km/ h, which is similar to that of the study by Swanson et al [38]. In this study, they demonstrated that the dogs were easily distracted at a lower treadmill speed, and the HR at a lower range of speed could hardly reflect exercise intensity [38]. Table 4: Correlation between individual heart rate and exercise intensity during continuous exercise or interval exercise.…”
Section: Discussionsupporting
confidence: 60%
“…Swanson and others described that dogs get easily distracted at lower treadmill speed. 20,51 At this time, these are only observations. It is necessary to wait for the results of this clinical trial, where several more questions will probably arise.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic exercise is commonly used in veterinary rehabilitation (13,14). While HR during exercise has been examined in athletic dogs, there are gaps in understanding what to expect, and data are lacking for rehabilitation patients (15)(16)(17)(18)(19)(20)(21)(22)(23). Swanson et al (19) developed a visual exertion scale for healthy dogs walking and trotting on a treadmill, finding that an increase in exertion correlated to an increase in HR.…”
Section: Introductionmentioning
confidence: 99%
“…Swanson et al (19) developed a visual exertion scale for healthy dogs walking and trotting on a treadmill, finding that an increase in exertion correlated to an increase in HR. The authors recognized that larger studies were needed to validate their subjective measures and that the Holter monitor used in that study may be prohibitively expensive to those in private practice (19). Boddy et al (20) described collecting HR by auscultation in a 6-min walk test in dogs with congestive heart failure as compared to normal healthy dogs: though post-walk HR did not significantly increase from baseline, distance traveled in the heart failure group was less.…”
Section: Introductionmentioning
confidence: 99%